Peran Sistem Database dalam Pengelolaan Data Retur Produk terhadap Efisiensi Operasional E-Commerce - Airin Putri Aulia Lubis; Muhammad Irwan Padli Nasution (International Forum of Researchers and Lecturers, 2026)
Advances in digital technology have transformed trade patterns, particularly in online buying and selling activities through e-commerce platforms. The rapid growth of e-commerce has increased the volume of online transactions, creating new challenges in managing operational data, especially product return data. Product returns are an important aspect of customer service because they directly affect customer satisfaction, inventory management, and business performance. Therefore, effective and structured data management is essential to ensure that return processes run efficiently and accurately. This study aims to determine the role of database systems in managing product return data and to analyze their impact on operational efficiency in e-commerce activities. The research employed a qualitative approach using a case study of Aulia Shop MSME. Data were collected through observation, interviews, and documentation to gain a comprehensive understanding of the return management process. The results indicate that the implementation of a database system significantly improves the management of product return data. The system accelerates data processing, minimizes recording errors, facilitates data retrieval, and simplifies the monitoring of returned products. In addition, database systems support the preparation of more organized, accurate, and systematic operational reports. Therefore, database systems play a crucial role in enhancing operational efficiency, improving decision-making processes, and supporting sustainable business operations in e-commerce environments.